A New Example to Art of the Depiction of the Westernization Era: Muğla Keyfoturağı Mosque - Ayşe Aydın (Art-Sanat)
Keyfoturağı Mosque is located in the Muğla Karabağlar Quarter, Yurtlar, and has a square plan. The name Kehfoturağı which comes from the names of the companions of the cave (Ashab al-Kahf) was written on the sanctuary wall of the mosque and has been transformed into Keyfoturağı in the course of time. The mosque was built in 1870 according to the inscription and was restored in 2005. The mural paintings located between the upper sanctuary windows are designed as square, transverse tetragon and rectangle panels. Inside these panels there are medallions inscribed with the names of the Prophet Muhammad, his grandsons, four caliphs and Ashab al-Kahf. These medallions are decorated with Baroque-Rococo style drapery, volute, acanthus, and C and S curved leaves. Two rectangular formed panels have date palms, two square formed panels have a sailboat on each, and one panelhas the depiction of the mosque surrounded by date palms and cypress trees. Besides the inscribed medallions, the inscriptions are placed within cartouches on one of the panels. It is apparent that some of the panels have vanished in the course of time, some motifs have been covered by whitewash during restorations, and some motifs have been retraced and appended. By using colour and chiaroscuro, volume is enhanced on the motifs of the decoration program and perspective trials have been made due to the western influenced drawing orders. The mural paintings of Keyfoturağı Mosque reflect the general characteristics of the Westernization era both by their themes and motifs, and by their technical and characteristic features. A deliberate study should be carried out in order to remove the traces of misguided restoration in Keyfoturağı Mosque which is a rare mosque having mural paintings in Muğla.